Effects of different sowing techniques on productivity and botanical composition of grass/clover mixture - Mladen Knežević; Josip Leto; Krešimir Bošnjak; Marina Vranić; Goran Perčulija; Hrvoje Kutnjak (Mljekarstvo)
In April 1999 field experiment was planted in Crkveni Bok near Sisak to evaluate the effect of different sowing techniques on productivity and botanical composition of grass/clover mixture. Seeding methods were: 1) direct seeding into corn stubble field with row distance of 18 cm (DSK18) or 2) 9 cm (DSK9), 3) conventional seeding (KS), 4) sod-seeding in existing pasture (RPTDS) and 5) natural meadow as control (KPT). Over the experimental period lasted from 1999 to 2001 the highest productivity in terms of fresh mass (FMY) and dry matter (DMY) yield was achieved by conventional seeding. The FMY and DMY achieved by KS technique (in average 38.84 t ha-1 and 7.11 t ha-1 respectively) was 7% and about 25% higher comparing with DSK9 and DSK18, respectively. The differences between the lowest FMY and DMY achieved on KPT and RPTDS were not statistically significant. DSK9 achieved 26% higher FMY and 18% DMY comparing with DSK18. The highest yield of grasses was achieved on DSK9 (3.38 t ha-1). The differences in the yield of grasses between KS and DSK18 were not statistically significant. The lowest yield of grasses had RPTDS (1.93 t ha-1) and KPT (1.97 t ha-1). The highest grass contribution to total DMY was determined on KPT (68.7%) and RPTDS (67.4%) while the lowest on KS (39.74%). The highest yield (3.19 t ha-1) and the highest legumes contribution to total DMY were determined in KS (44.8%), while the lowest in KPT (0.28 t ha-1 and 9.8% respectively) and DSK18 (0.38 t ha-1 and 13.2% respectively). The lowest yield of forbs was determined on RPTDS (0.55 t ha-1) and the lowest forbs contribution to total DMY on DSK9 (12.8%) and KS (15.45%).